2003
DOI: 10.1046/j.1440-1754.2003.00174.x
|View full text |Cite
|
Sign up to set email alerts
|

Maternal phenylketonuria in Western Australia: Pregnancy outcomes and developmental outcomes in offspring

Abstract: Poor metabolic control in pregnancy is associated with poorer cognitive outcomes and increased behavioural difficulties in offspring of mothers with PKU. The results have implications for the implementation of appropriate dietary measures before conception in PKU pregnancies, and indicate a need for the establishment of multidisciplinary teams to follow up individuals with PKU to communicate the importance of pregnancy planning, to manage PKU pregnancies, and to follow up the offspring.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2005
2005
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 29 publications
0
7
0
Order By: Relevance
“…There is emerging evidence of adverse behavioral outcomes, including externalizing behaviors, in children born to women with suboptimal PHE control during pregnancy. 55 Microcephaly is the most common fetal malformation associated with elevated maternal PHE levels during gestation. The incidence of microcephaly increases to 5-18% with achievement of control by 10 weeks gestation and steadily increases to 67% if PHE control is not achieved by 30 weeks gestation.…”
Section: Clinical Featuresmentioning
confidence: 99%
“…There is emerging evidence of adverse behavioral outcomes, including externalizing behaviors, in children born to women with suboptimal PHE control during pregnancy. 55 Microcephaly is the most common fetal malformation associated with elevated maternal PHE levels during gestation. The incidence of microcephaly increases to 5-18% with achievement of control by 10 weeks gestation and steadily increases to 67% if PHE control is not achieved by 30 weeks gestation.…”
Section: Clinical Featuresmentioning
confidence: 99%
“…Significant planning is required for pregnancies for women with phenylketonuria (PKU) as elevated levels of blood phenylalanine (Phe) during pregnancy causes negative birth outcomes such as pregnancy losses, congenital heart disease, and other developmental problems such as intellectual disability [18], [25]. These adverse outcomes are common, for example Lenke and Levy [14] reported that in women with Phe levels > 20 mg per decilitre, 73% had microcephaly and 92% of children had intellectual disabilities.…”
Section: Introductionmentioning
confidence: 99%
“…In WA, babies born to mothers with PKU were tracked over a 9‐year period 6 . Thirty pregnancies resulted in 16 live births for nine women, with no congenital abnormalities recorded, although there was some evidence of behavioural problems among children where metabolic control was poor during pregnancy.…”
mentioning
confidence: 99%